A mystagogical view of 'withness' in entrepreneurship education. Issue 2 (April 2017) - Refai, Deema; Higgins, David
This article provides a philosophical conceptualization of how learners engage in entrepreneurial learning from within by focusing on the role of the inner identity and mission of the learner. Klapper and Neergaard add 'withness' to the learning frameworks of entrepreneurship education (EE), but there is scant literature discussing the implications of learning from within in this context. Fayolle calls for an investigation of how learners learn in order to address the vast differences among audiences in EE and thus to understand the rationale behind 'effective didactical design'. This article adopts a postmodernist perspective to understand the role of the self in EE and draws on the learning onion model for learning from within. A mystagogical perspective is proposed to help learners engage with their inner missions and identities and improve their core reflection skills, thus highlighting an inspirational dimension of EE.